2013
DOI: 10.1614/wt-d-12-00159.1
|View full text |Cite
|
Sign up to set email alerts
|

Aminocyclopyrachlor Efficacy for Controlling Virginia Buttonweed (Diodia virginiana) and Smooth Crabgrass (Digitaria ischaemum) in Tall Fescue

Abstract: Virginia buttonweed and smooth crabgrass are problematic weeds in tall fescue and may warrant control with herbicides at similar timings. The objectives of these field experiments were to evaluate (1) aminocyclopyrachlor rate and application regimens for controlling Virginia buttonweed and (2) the influence of growth stage on aminocyclopyrachlor efficacy for controlling smooth crabgrass. Single applications of aminocyclopyrachlor at 0.05 and 0.08 kg ai ha−1 provided poor (< 70%) and fair (70 to 79%) control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…In the present study, we evaluated the effectiveness of using a single DCNN to detect multiple weed species growing in perennial ryegrass. Simultaneous detection of multiple weed species is of paramount importance for precision herbicide application because weeds often grow in mixed stands and various postemergence herbicides, such as 2,4-D, carfentrazone, dicamba, and MCPP, are sprayed to provide broad-spectrum control of various broadleaf weeds (McElroy and Martins, 2013; Reed et al, 2013). For training purposes, E. maculata, G. hederacea , and T. officinale constituted a single category of objects to be discriminated from perennial ryegrass ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we evaluated the effectiveness of using a single DCNN to detect multiple weed species growing in perennial ryegrass. Simultaneous detection of multiple weed species is of paramount importance for precision herbicide application because weeds often grow in mixed stands and various postemergence herbicides, such as 2,4-D, carfentrazone, dicamba, and MCPP, are sprayed to provide broad-spectrum control of various broadleaf weeds (McElroy and Martins, 2013; Reed et al, 2013). For training purposes, E. maculata, G. hederacea , and T. officinale constituted a single category of objects to be discriminated from perennial ryegrass ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These weed species are commonly found in various cool-season turfgrasses. Herbicides, such as 2,4-D, dicamba, MCPP, triclopyr, and sulfentrazone are broadcast-applied in cool-season turfgrasses for POST control of various broadleaf weeds (McElroy and Martins, 2013; Reed et al, 2013; Johnston et al, 2016; Yu and McCullough, 2016a; Yu and McCullough, 2016b). Precision herbicide application using machine-vision based sprayers will substantially reduce herbicide input and weed control costs.…”
Section: Introductionmentioning
confidence: 99%
“…ex Muhl.] (Reed et al 2013), and wheat (Triticum aestivum L.), even when applied to fallow ground before planting winter wheat (Kniss and Lyon 2011). Because of the observed effect of aminocyclopyrachlor on reducing seed production in these graminoids, a study was conducted to evaluate the potential effect of aminocyclopyrachlor on the important exotic annual grass downy brome.…”
mentioning
confidence: 99%
“…However, when these herbicides were applied sequentially, the defoliation rate was 95%. Other information in the literature about the efficacy of aminocyclopyrachlor + metsulfuronmethyl in the control of weed plants was reported by Reed et al (2013), West et al (2011), Ferrel et al (2012 and Kyser and DiTomaso (2013). These authors found that this product was effective in the control of Diodia virginiana, Lantana camara, Cayratia japonica and Linaria dalmatica.…”
Section: Resultsmentioning
confidence: 92%